(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the morphological characteristics of bacteria include not only the shape, but also the size of the cells, the location of the cells in the cavity, the presence of spores. The morphology of bacteria depends on the conditions of growth in nutrients, environment, temperature and other factors. The most typical morphology of bacteria is found in young cultures. Bacteria are microorganisms that are widely distributed in nature and do not have a real complex structured nucleus. Bacteria are single-celled organisms that differ in size and physiological characteristics.